Serum glucose levels for predicting death in patients admitted to hospital for community acquired pneumonia: prospective cohort study. (29th May 2012) - Lepper, Philipp M; Ott, Sebastian; Nüesch, Eveline; von Eynatten, Maximilian; Schumann, Christian; Pletz, Mathias W; Mealing, Nicole M; Welte, Tobias; Bauer, Torsten T; Suttorp, Norbert; Jüni, Peter; Bals, Robert; et al.
Abstract : Objective To examine whether acute dysglycaemia predicts death in people admitted to hospital with community acquired pneumonia. Design Multicentre prospective cohort study. Setting Hospitals and private practices in Germany, Switzerland, and Austria. Participants 6891 patients with community acquired pneumonia included in the German community acquired pneumonia competence network (CAPNETZ) study between 2003 and 2009. Main outcome measures Univariable and multivariable hazard ratios adjusted for sex, age, current smoking status, severity of community acquired pneumonia using the CRB-65 score (confusion, respiratory rate >30/min, systolic blood pressure ≤90 mm Hg or diastolic blood pressure ≤60 mm Hg, and age ≥65 years), and various comorbidities for death at 28, 90, and 180 days according to serum glucose levels on admission. Results An increased serum glucose level at admission to hospital in participants with community acquired pneumonia and no pre-existing diabetes was a predictor of death at 28 and 90 days. Compared with participants with normal serum glucose levels on admission, those with mild acute hyperglycaemia (serum glucose concentration 6-10.99 mmol/L) had a significantly increased risk of death at 90 days (1.56, 95% confidence interval 1.22 to 2.01; P<0.001), and this risk increased to 2.37 (1.62 to 3.46; P<0.001) when serum glucose concentrations were ≥14 mmol/L. In sensitivity analyses the predictive value of serum glucose levels on admission for death was confirmed at 28 days and 90 days. Patients with pre-existing diabetes had a significantly increased overall mortality compared with those without diabetes (crude hazard ratio 2.47, 95% confidence interval 2.05 to 2.98; P<0.001). This outcome was not significantly affected by serum glucose levels on admission (P=0.18 for interaction). Conclusions Serum glucose levels on admission to hospital can predict death in patients with community acquired pneumonia without pre-existing diabetes. Acute hyperglycaemia may therefore identify patients in need of intensified care to reduce the risk of death from community acquired pneumonia.